A paradigm shift in Natech risk management: Development of a rating system framework for evaluating the performance of industry. (January 2022) - Suarez-Paba, Maria Camila; Cruz, Ana Maria
Abstract: An increasing trend in the number of reported natural hazard-triggered technological accidents (Natechs) worldwide has led to the development of contributions in Natech risk assessment and management, risk reduction and emergency response strategies, risk communication, risk perception, and risk governance. Yet, although some studies have underscored the need for resilient industries, only recently researchers have called for an area-wide perspective, where a paradigm shift in Natech risk management fosters a holistic systems approach. That approach should contemplate the facilities and their surrounding environment, and encourage multi-stakeholder interaction to advocate for more resilient societies. However, there are currently no methodologies for evaluating, rating, and certifying industrial facilities' level of preparedness to Natech risk; nor are there any tools available to inform the governments and the public, on industry's Natech risk management practices. In response to this need, we propose Natech RateME, a comprehensive, area-wide risk management, and rating system framework. The proposed framework is premised on a probabilistic risk assessment methodology, that can support industrial facilities' management of onsite and offsite risk from complex events and that rates their performance in terms of minimum life losses. By evaluating their safety performance, their engagement to develop cooperation mechanisms with local authorities and neighboring communities, and their commitment to disclose risk information, among other aspects, the framework, and the rating system, seek to contribute to overall territorial resilience. To do so, Natech RateME considers the interaction between infrastructure systems present at industrial parks, the technical and organizational systems, governance, risk communication, and community participation, constituting the first approach to support the strengthening of prevention and mitigation measures by enhancing facilities' and governments' abilities to manage Natech risk comprehensively. Highlights: Comprehensive Natech area-wide risk management and rating system framework. Interconnection of key factors and stakeholders at industrial facilities' location. Industry and government abilities enhancement to manage Natech risk comprehensively. A paradigm shift in Natech risk management with resilience engineering notions.